Electrochemical determination of novel psychoactive substances by differential pulse voltammetry using a microcell for boron-doped diamond electrode and screen-printed electrodes based on carbon and platinum - González Hernández, Jerson (2021)
25B-NBOMe, benzylpiperazine (BZP), 1-(3-chlorophenyl)piperazine (mCPP), and N,N-dimethyltryptamine (DMT) are potent hallucinogenic and stimulant drugs which have emerged as novel psychoactive substances (NPS). The electroanalytical behavior of these compounds was investigated by differential pulse voltammetry (DPV) on boron-doped diamond (BDD) electrode assembled in a homemade microcell, and disposable screen-printed electrodes based on bare carbon (SP-C) and platinum (SP-Pt). The low-cost micro-method proposed in this paper requires volume ranging from 50 L to 100 L, minimal sample preparation, and generates very few residues. The electrochemical screening exhibited anodic peaks studied by linear regression of five-point analytical curves (n=3) which allowed for estimating the sensitivity, limits of detection (LOD) and quantification (LOQ), repeatability (S_r), and intermediate precision (S_RW). These results translate into methods with high sensitivity, satisfactory precision (range of 1.7 % to 9.0 %) and low limits of detection (LOD from 0.15 µg/mL to 1.8 µg/mL) with analytical value in clinical and forensic techniques. Accuracy and applicability of the voltammetric method was assessed in spiked oral fluid samples by standard additions calibration curves with recovery ranging from 98 % to 103 %. For the first time, the electrochemical data obtained by DPV on three different working electrodes and the analytical parameters are compared for these NPS.